ACCESSIBILITY OF EDUCATION AND SUPPORT FOR A LEARNER AFTER FORMAL EDUCATION: A CASE OF LITHUANIA - Dudaitė, Jolita; Indrašienė, Valdonė; Jegelevičienė, Violeta; Prakapas, Romas (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Access to education and support for a learner is among the most important educational policy and management issues in the context of educational reform. In many European countries, both academics and practitioners are looking for optimal ways to ensure the child's well-being through the implementation of the principle of access to education, which, as it is known, contributes to reducing social exclusion and, at the same time, increasing academic success. One of the possible means to implement these goals is the idea of the all-day school. Several patterns of the implementation of this idea in Europe can be detected. However, there is often a lack of arguments about the meaningfulness and feasibility of creating such all-day school models. With a view to solving that problem from the perspective of stakeholders and applying a strategy of case study, a comprehensive analysis was carried out in order to find out the need for education, health, social and cultural services for children in Lithuania. In Lithuania, the length of the school year was extended from 2017–2018. It raised a number of issues related to the package of education and social services can be incarnated at school. The discussion about the need to extend working hours in school created preconditions for talking about the wider possibilities of providing additional education, health, social and cultural services at school. Thus, a representative parental survey was conducted to determine the need for additional education, health, social and cultural services at school and the need for all-day school in general. A sample of 1615 parents from all 10 Lithuanian counties was selected. The results of the research are valuable for the discussion of the researchers of educational sciences.